Exploring edamame survival mechanisms under combined drought and heat stress: Photosynthesis efficiency and carbohydrate accumulation - Jeremiah M. Hlahla; Mpho S. Mafa; Rouxléne van der Merwe; Makoena J. Moloi (Plant Stress)
The combined drought and heat (DH) stress have devastating effects on plant physiological and biochemical processes, leading to poor yield. The aims of this study were to identify the physio-biochemical mechanisms employed by edamame (Glycine max L. Merrill) for survival and to establish better performing cultivars under DH stress. The impact of DH stress on the photosynthesis efficiency and osmolytes production in three edamame cultivars (UVE14, UVE17 and AGS429) was investigated. Non-destructive measurements were performed to determine the photosynthesis attributes, while pigments, non-structural carbohydrates (starch, glucose, sucrose, trehalose) and proline were extracted and quantified spectrophotometrically. The results showed that chlorophyll a (Chl-a), Chl-b, total chlorophyll and carotenoids in AGS429 were not affected under DH stress, which corresponded to increased normalised difference vegetative index (NDVI). Positive correlations between the carotenoids and total chlorophyll contents suggest that in AGS429, prevention of chlorophyll degradation under DH stress could be attributed to the increased carotenoids because they have antioxidative function. Additionally, AGS429 and UVE14 had increased trehalose, suggesting high osmotic adjustment under DH stress. An increase in starch production maintained glucose balance in AGS429 and UVE14, demonstrating higher photosynthetic efficiency compared to UVE17. The DH stress reduced photochemical reactions and carbohydrate accumulation in UVE17. This study shows that AGS429 and UVE14 protected the photosystems and photosynthetic pigments during DH stress, which led to higher photosynthetic capacity and accumulation of carbohydrates. Thus, maintaining the photosynthesis efficiency and carbohydrate metabolism processes in the AGS429 and UVE14 were adaptation features under DH stress.